MUC1 oncogene amplification correlates with protein overexpression in invasive breast carcinoma cells - Lacunza, Ezequiel (2010)
The MUC1 gene is aberrantly overexpressed in approximately 90% of human breast cancers. Several studies have shown that MUC1 overexpression is due to transcriptional regulatory events. However, the importance of gene amplification as a mechanism leading to the increase of MUC1 expression in breast cancer has been poorly characterized. The aim of this study was to evaluate the role of MUC1 gene amplification and protein expression in human breast cancer development. By means of real-time quantitative polymerase chain reaction and immunohistochemical methods, 83 breast tissue samples were analyzed for MUC1 gene amplification and protein expression. This analysis showed MUC1 genomic amplification and a positive association with the histopathological group in 12% (1 out of 8) of benign lesions and 38% (23 out of 60) of primary invasive breast carcinoma samples (P = 0.004). Array-comparative genomic hybridization meta-analysis of 886 primary invasive breast carcinomas obtained from 22 studies showed MUC1 genomic gain in 43.7% (387 out of 886) of the samples. Moreover, we identified a highly statistical significant association between MUC1 gene amplification and MUC1 protein expression assessed by immunohistochemistry and Western blot test (P < 0.0001). In conclusion, this study demonstrated that MUC1 copy number increases from normal breast tissue to primary invasive breast carcinomas in correlation with MUC1 protein expression.